SOLUSI PROBLEMATIKA PENYIDIKAN DALAM KERANGKA EFEKTIVITAS SISTEM PERADILAN PIDANA DAN REKOMENDASI PEMBENTUKAN LEMBAGA âPENYIDIKAN LANJUTANâ DALAM PEMBAHARUAN KUHAP - Gunakaya, A. Widiada (Jurnal Wawasan Yuridika, 2011)
Criminal Justice System is a method of crime prevention by means of the Criminal Code. The way it works by actualizing, concretizing, functionalizing, and operationalizing the provisions of the Criminal Law in a criminal justice mechanism. The goal is to solve crimes as quick as possible by completing criminal matters into submission. To achieve its objectives, the components must work together in a systemic justice in all phases of criminal justice. But at the level of investigation as a prejudice stage, found problems with noncompliance with the formal and substantive requirements of an investigation. Consequently action of "preaccusation", and such incidents often occur repeatedly. The access; there is accumulation of matter at the level of investigation. On the other hand, in the case of certain crimes, the problem of authority is also investigating a collision occurred between the Police Investigator with the Civil Servant. Some policyrelated legislative, even eliminate the authority of the Police as an investigator. Problem solving of legal problems over the required solution. First of yuridik investigation techniques while referring to the "legislated" environment, applying the principle of due process of law and not marginalize the living law. Second, in order to reform the Criminal Procedure Code recommended a procedural policy of "Institute of Advanced Investigation" to meet the speedy trial principle in the framework of effectiveness of Criminal Justice System.Keywords: Criminal Justice System â Investigation " Institute for Advanced Investigation".